2007
DOI: 10.1080/02705060.2007.9665037
|View full text |Cite
|
Sign up to set email alerts
|

Possible Seasonal Population Bottlenecks In Brook Trout (Salvelinus fontinalis) in Central Appalachian Headwater Streams

Abstract: Brook trout (Salvelinus fontinalis) in the Appalachian Mountains often inhabit low production streams that limit growth. Therefore, we examined seasonal changes in body composition of age-1 and older brook trout to identify critical periods of growth or depletion that may lead to mortality and determined if brook trout in headwater streams reached critical levels of resource depletion over winter. Six streams in the central Appalachian Mountains in West Virginia containing naturally reproducing brook trout wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Although salmonids have not always been found to deplete lipid reserves over winter (Webster & Hartman, 2007), several studies have reported declines in lipid content and increases in water content in overwintering fishes similar to those reported here (Cunjak & Power, 1986; Biro et al, 2004). Salmonid winter feeding is restricted because low water temperatures limit appetite, digestion and gastric evacuation rates (Cunjak et al , 1987; Sweka et al, 2004); consequently they primarily rely upon stored fat to meet energetic demands, and thus can lose mass during this period (Cunjak et al , 1987).…”
Section: Discussionsupporting
confidence: 81%
“…Although salmonids have not always been found to deplete lipid reserves over winter (Webster & Hartman, 2007), several studies have reported declines in lipid content and increases in water content in overwintering fishes similar to those reported here (Cunjak & Power, 1986; Biro et al, 2004). Salmonid winter feeding is restricted because low water temperatures limit appetite, digestion and gastric evacuation rates (Cunjak et al , 1987; Sweka et al, 2004); consequently they primarily rely upon stored fat to meet energetic demands, and thus can lose mass during this period (Cunjak et al , 1987).…”
Section: Discussionsupporting
confidence: 81%
“…Although almost all individuals gained weight throughout the ice-covered period in our study, we cannot rule out that starvation was a significant cause of the observed overwinter mortality. However, there are indications that also other streamdwelling charrs (e.g., Salvelinus fontinalis) suffered little from starvation during the winter (Webster & Hartman 2007). Overall, we observed relatively low mortality and thus, size-dependent survival should probably not be expected to be prominent.…”
Section: Discussionmentioning
confidence: 53%
“…The overall density of charr in the experimental brook was lower compared to fish density in other subarctic rivers and streams (Gabler & Amundsen 1999;Gabler et al 2001;Jensen 2004), and generally, stream-dwelling salmonids have low antagonistic behaviour during winter with low temperatures and light intensities typically for under ice conditions (reviewed by Huusko et al 2007). However, there are indications that also other streamdwelling charrs (e.g., Salvelinus fontinalis) suffered little from starvation during the winter (Webster & Hartman 2007). Although almost all individuals gained weight throughout the ice-covered period in our study, we cannot rule out that starvation was a significant cause of the observed overwinter mortality.…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, future studies should move beyond reporting proximate composition on a TBM basis and compare percentage-based models of morphology with those including BIA metrics to gauge the actual benefit of using this tool in field operations. Many studies to date have included morphometric and BIA (or just BIA) metrics as candidate predictors in models without including a morphometric-only model by which to evaluate the added utility of BIA (Cox and Hartman 2005;Duncan 2007;Webster and Hartman 2007;Hanson et al 2010). The addition of BIA metrics to our percentage-based morphometric models only increased the proportion of explained variance marginally (as much as 4% across species), such that the effort of taking BIA measurements in addition to length and wet-mass measurements is likely not worth the gain in predictive power.…”
Section: Estimating Fish Condition: Considerations For Future Studiesmentioning
confidence: 99%